Synthesis and olfactory properties of Phantolide analogues in racemic and optically active forms. (11th December 2018) - Kawasaki, Masashi; Kuroyanagi, Saki; Ito, Takuya; Morita, Hiroyuki; Tanaka, Yasuo; Toyooka, Naoki
Abstract: The racemates, ( + )‐ and ( – )‐enantiomers, of eight novel Phantolide analogues, which are non‐natural musk odorants, were synthesized. The key step of the asymmetric synthesis was the lipase‐catalysed enantioselective transesterification of a racemic primary alcohol, and the resultant two enantiomers of the primary alcohol were used as intermediates for further transformations. The odour profiles of all of the synthesized Phantolide analogues were evaluated. Some interesting findings on the odour profiles of the analogues are reported here. Abstract : The racemates, ( + )‐ and ( – )‐enantiomers of eight novel Phantolide, a representative non‐natural musk odorant, analogues were synthesized. The odor profiles of all the synthesized phantolide analogues were evaluated